Preventive Gastroprotective Effect of a Functional Food Based on Quinoa (Chenopodium quinoa Willd.) and Quercetin in a Murine Model of Ibuprofen-Induced Gastric Damage - Maribel Valenzuela-González; José Luis Cárdenas-López; Armando Burgos-Hernández; Norma Julieta Salazar-López; Manuel Viuda-Martos; Mónica A. Villegas-Ochoa; Gustavo Martínez-Coronilla; J. Abraham Domínguez-Avila; Shela Gorinstein; Gustavo A. González-Aguilar; Rosario Maribel Robles-Sánchez (Antioxidants, 2025)
Nonsteroidal anti-inflammatory drug-based therapies are the cause of 20–30% cases of gastric lesions in chronic users worldwide. Co-medication with omeprazole (OMP) is the most commonly used option to prevent these lesions, although this carries risks of its own; thus, alternatives are being explored, such as dietary antioxidant therapies. The objective of this study was to evaluate the gastroprotective activity of quinoa (Chenopodium quinoa Willd.) on ibuprofen (IBP)-induced gastric ulcers in a rat model. Quinoa cookies were formulated with heat-treated quinoa using microwave radiation. The intestinal bioaccessibility of phenols and flavonoids, and the antioxidant activity of microwaved quinoa cookies (MQCs) were notably higher than quinoa cookies without thermal treatment (RQCs): 132% TPC, 52% TFC, 1564% TEAC vs. 67% TPC, 24% TFC, and 958% TEAC, respectively. Basal diets were supplemented with MQCs (20%) and quercetin (Q, 0.20%) as a reference flavonoid and administered for 30 days. Gastric lesions were induced by intragastric IBP doses, with OMP treatment as a positive control. Gastric damage index (macroscopic study), histological score (microscopic study), and plasma antioxidant enzyme activity (SOD and CAT) were evaluated. Macroscopic results showed that the addition of MQCs, Q, and OMP decreased the gastric damage index (GDI) by 50%, 40%, and 3%, respectively, as compared to IBP (GDI 100%). Histological analyses showed neutrophil infiltration and congested blood vessels in IBP-treated tissues; in contrast, the experimental diet groups showed lower infiltration for MQC > OMP > Q, respectively. A significant increase in SOD and CAT enzyme activity was observed in the MQC and Q groups as compared to the IBP group. We conclude that a reduction in the GDI and histological score was observed in IBP-induced murine models fed diets containing 20% MQC and 0.20% Q, demonstrating a preventive gastroprotective effect.